THE ROLE OF PRINCIPAL LEADERSHIP ON TEACHER’S PERFORMANCE OF PRIMARY SCHOOL TEACHER - - Supriyati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
The quality of education is determined by teacher performance because teachers are a central factor in the delivery of education. Principal leadership is needed as an effort to improve teacher performance. This study aims to determine the role of principal leadership on the performance of public elementary school teachers in Gunungwungkal District, Pati Regency. This research is a descriptive research. Data collection techniques using documentation, interviews, and questionnaires. The results showed (1) the role of the principal as an educator, namely involving teachers in seminars, training and workshops; (2) the role of the principal as manager, which is to regulate the division of teacher duties according to their main duties and functions; (3) the principal's role as administrator, namely managing personnel administration, learning administration, and financial administration; (4) the role of the principal as a supervisor, namely supervising teachers; (5) the role of the principal as a leader, namely leading in decision making; (6) the role of the principal as an innovator, namely developing innovative programs (7) the role of the principal as a motivator, namely providing motivation and encouragement to teachers. Keywords: role, leadership, principal, performance, teacher